Minicutting technique from ministumps originating from grafting of adult Surinam cherry - Peña Peña, Martha Lucía; Zanette, Flávio; Biasi, Luiz Antonio (Comunicata Scientiae, 2015)
The aim of this study was to evaluate the viability of the minicutting technique in the vegetative propagation of Surinam cherry (Eugenia uniflora L.), through productivity and survival of ministumps, and rooting of minicuttings originating from grafting and treated with different concentrations of indolebutyric acid (IBA) in the successive collections. The ministumps were obtained through grafting (cleft graft) of scions collected from the selected tree onto rootstock formed by seeds collected from the same tree. To create the minigarden, the grafted seedlings were grown in root plugs and their sprouts were pruned, maintaining one pair of leaves on each sprout. From these ministumps, successive collections of sprouts (minicuttings) were made. A completely randomized experimental design was used in a 4 x 4 factorial arrangement (four periods of collection of minicuttings x four concentrations of IBA), with four replications and 20 minicuttings as an experimental unit. The survival rate of the ministumps was 100% after four successive collections of sprouts. In the higher temperature period was possible to carry out two collections of shoots. Mean yield was 2.4 minicuttings/ministump, 598.9 minicuttings/m2 in the first collection time, and 2.7 minicuttings/ministump, 681.1 minicuttings/m2 in the second collection time. Mean yield was 384.4 minicuttings/m2 /month. It was adventitious rooting of less than 1.9%. The rooting of minicuttings from grafting of the Surinam cherry is not favored with the use of IBA.